The Close Encounter Between Alpha-Synuclein and Mitochondria - Vicario, Mattia; Cieri, Domenico; Brini, Marisa; Calì, Tito (Frontiers in Neuroscience, 2018)
The presynaptic protein alpha-synuclein (α-syn) is unequivocally linked to the development of Parkinson’s disease (PD). Not only it is the major component of amyloid fibrils found in Lewy bodies but mutations and duplication/triplication in its gene are responsible for the onset of familial autosomal dominant forms of PD. Nevertheless, the precise mechanisms leading to neuronal degeneration are not fully understood. Several lines of evidence suggest that impaired autophagy clearance and mitochondrial dysfunctions such as bioenergetics and calcium handling defects and alteration in mitochondrial morphology might play a pivotal role in the etiology and progression of PD, and indicate the intriguing possibility that α-syn could be involved in the control of mitochondrial function both in physiological and pathological conditions. In favor of this, it has been shown that a fraction of cellular α-syn can selectively localize to mitochondrial sub-compartments upon specific stimuli, highlighting possible novel routes for α-syn action. A plethora of mitochondrial processes, including cytochrome c release, calcium homeostasis, control of mitochondrial membrane potential and ATP production, is found directly influenced by α-syn. Eventually, α-syn localization within mitochondria may also account for its aggregation state, making the α-syn/mitochondria intimate relationship a potential key for the understanding of PD pathogenesis. Here, we will deeply survey the recent literature in the field by focusing our attention on the processes directly controlled by α-syn within mitochondrial sub-compartments and its potential partners providing possible hints for future therapeutic targets.